Short-Term Effect of Wheat Residue Burning on Soil Properties in Chitwan - Aryal, Krishna; Gairhe, Janmajaya; Bhusal, Aashika; Subedi, Barsha (Journal of the Institute of Agriculture and Animal Science, 2025)
Crop residue burning is widely practiced in terai region of Nepal as it is cheap, easy, and convenient method for managing post-harvest crop remnants. Although burning practice is commonly perceived to rapidly improve soil fertility, its immediate effects on soil properties remain poorly understood. This study examined the short-term effects of wheat residue burning on key physico-chemical soil properties across three sites viz: Phasera, Jamauli and Salauli of Khairahani Municipality, Chitwan, Nepal. A total of 180 soil samples (30 pre-burn and 30 post burn) from each site were collected during the time of wheat harvest at the depth of 0-15 cm. A paired t-test compared pre- and post-burn conditions for bulk density, particle density, pH, organic matter (OM), total nitrogen (TN), available phosphorus (P), and potassium (K). Results revealed site-specific response to burning. Bulk density remains unaffected across the sites while pH (5.62±0.56 to 6.01±0.73; p < 0.01) increased significantly at Phasera. Similarly, OM and TN showed limited changes except at Salauli, available P declined markedly at Jamauli (142.67±79.88 mg kg-1 to 91.88±81.91 mg kg-1; p<0.01) while available K increased significantly across all the sites. The findings demonstrate that residue burning induces complex, nutrient-specific shifts, with short-term benefits of pH increment and K release, however it increases the risk of P loss and inconsistent OM response. Therefore, further investigation of the long-term impacts of residue burning on soil health is essential, considering post burning sampling time, burning intensity, and residue volume.